Evaluating the role of prosumers in providing energy systems with flexibility products - Amir Esmaeili‐Nezhad; Sara Ostovar; Moein Moeini‐Aghtaie (The Journal of Engineering)
Abstract Increasing the penetration of renewables on the demand side causes operational challenges in distribution grids due to their variable and uncertain behaviour. These resources have increased distribution grid net load fluctuation during recent years, which needs to be covered by demand side flexibility (DSF). DSF should be quantified and measured by a suitable index to show the level of a system DSF in different situations. In this paper, the flexibility area index of distribution systems as a suitable metric for prosumers’ DSF evaluation, especially in the presence of renewable sources, is calculated. This index is defined first for one prosumer and then extended to a distribution system by a combination of prosumer indices. The mentioned index is decomposed into two components, one for ramp‐up (negative flexibility) and another for ramp‐down (positive flexibility). To calculate and manage prosumers’ flexibility, a novel flexibility‐oriented stochastic framework for prosumers is suggested. The amount of load shedding is under control by the risk‐management strategy in the proposed framework, which can facilitate distribution system operator operation. The results obtained from the implementation of the case study validate the major features of the proposed framework more efficiently.